EFFECTS OF BRIEF-INTENSE MODE AND ACUPUNCTURE-LIKE TENS IN THE RELIEF OF CHRONIC LOW BACK PAIN (Journal of Biomedical Investigation, 2023)
Background: Transcutaneous electrical nerve stimulation (TENS) is a physical modality used in the management of pain using various treatment modes. However, the optimal mode of application for the treatment of chronic low back pain appeared not to be well studied.Aim: The study aimed to determine and compare the effects of Brief-intense mode and Acupuncture-like TENS in the relief of chronic low back pain.Materials and Methods: Twenty-seven (27) participants were recruited using a consecutive sampling technique. Participants were randomly allocated into three groups (Brief-intense, Acupuncture-like TENS and Control group) using simple balloting. Participants in brief-intense group and acupuncture-like TENS group received TENS treatment using different current intensities, pulse duration and frequency in addition to conventional physiotherapy treatment for low back pain. However, participants in control group received only conventional physiotherapy treatment for low back pain. Each group received treatment two times a week for six weeks. Outcome measures assessed were pain intensity and functional disability using Numerical Pain Rating Scale (NPRS) and Roland Morris  Questionnaire (RMQ) respectively. Data collected at baseline, week three and six were analyzed using using one-way ANOVA and independent Ttest. Alpha level was set at < 0.05.Results: There was a significant reduction in pain intensity and functional disability in the three groups across the three time frame for measurement (p < 0.05). However, there was no significant difference between the effects of Brief-intense mode and Acupuncture-like TENS on pain intensity and functional disability (p > 0.05).Conclusion: Both modes of TENS (brief-intense group, acupuncture-like TENS) produced a significant effect in the reduction of pain as well in the improvement of functional disability in all participants with chronic low back pain. However, no one seems to be more effective than the other in the treatment of chronic low back pain.
Keywords: low back pain; Transcutaneous electrical nerve stimulation; Brief-intense TENS